Evolution of freshwater cage culture in India and role of ICARCIFRI - retrospect and prospect - Das, A K; Das, B K (Journal of the Inland Fisheries Society of India, 2021)
Cage aquaculture, though an in-built component of aquaculture in India and South East Asia since time immemorial, has been put forth by ICAR-CIFRI in inland open waters of India from 1970s with renewed interests that spread to different inland open water resources with time. The technology achieved strong foothold towards in situ production of stocking materials for reservoirs under a CGIAR project during 2006-2009, followed by production of table fish with diversified species successfully utilizing financial assistance of NFDB, Hyderabad. The outcome was adoption of the technogy initially by 12 States under NMPS project of DAHD&F, GoI, followed by additional 5 States in Mission mode. The phenomenal success of this trchnology has been well accepted and implemented now by 20 States in their reservoirs and wetlands with more than 20,000 cages in functional mode across India. The technology has been wrapped into commercialization of CIFRI GI Model Cage followed by CIFRI Cage Grow Feed. The inland cage culture development in India, ushered by ICAR-CIFRI, with the passage of time is chronologically depicted here. ICARCIFRI has been instrumental in upscaling the technology, in designing and fabrication of low cost cages and diversification of economically important high value fish species, a step forward towards developing blue economy targeting Second Blue Revolution. The technology has also been well adopted in PMMSY-2020 with targeted installation of 20,000 new cages in different states in coming five years, which is a testimony to significance of this noble technology in boosting rural economy further. Key words Cage culture, Reservoir, Wetland, Seed raising, Table fish, Blue Revolution, India